Work conditions and midwives labor suffering : A filed study in the hospitals of Constantine commune - Mouhoub, Abdellah; khallassi, Mourad (Journal of Human Sciences, 2021)
This study aimed to know the different types of occupational conditions, physical, human, organizational and material, that make midwives suffer in their work, in addition to knowing the suffering at work and its indicators. The study was conducted in some hospital of the state of Constantine and we relied on the descriptive approach using the content analysis method. the study sample consisted of 12 cases from three hospitals .The interview was used as a tool to collect information and this is after building a network of interviews related to working conditions and others related to suffering .The study concluded with identifying the various conditions that lead to suffering at work ,the most important are :the lack of work tools ,lack of hygiene, overcrowding, lack of pay, excessive working hours, exposure to various attacks from patients or their families ,difficulty communicating with supervisors in order to communicate their various concerns. These circumstances were also adopted as indicators through which to infer the phenomenon of suffering at work, who’s indicators are psychological pressure, role, ambiguity, stress ,violence.